Textual Differences in Alexander von Humboldt’s "Essai politique sur l’île de Cuba". An editorial commentary on the first volume of the „Humboldt in English“ (HiE) book series - Kraft, Tobias (HiN - Alexander von Humboldt im Netz. Internationale Zeitschrift für Humboldt-Studien, 2012)
Zusammenfassung Die vorliegende Studie basiert auf einem Editionsbericht, der 2009 im Rahmen der Konferenz „Alexander von Humboldt and the Hemisphere“ an der Vanderbilt University (Nashville, TN) vorgestellt wurde. Die für diese Publikation weiter entwickelte Untersuchung verdeutlicht die Textgenese von Humboldts Essai politique sur l’île de Cuba auf der Basis eines Textvergleichs zwischen allen drei „Originalquellen“ des Texts. Der hier in seinen Ergebnissen vorgestellte Textvergleich ist Teil des Editionsprojektes „Humboldt in English“ (HiE), bei dem sich ein US-deutsches Editorenteam seit 2007 zum Ziel gesetzt haben, kritische Neuübersetzungen von drei wichtigen Schriften aus Humboldts „Opus Americanum“ anzufertigen (s.a. Fußnote). Der Textvergleich des Essai politique sur l’île de Cuba bildete die Textgrundlage für den ersten Band der HiE-Reihe, den 2011 bei Chicago University Press erschienenen The Political Essay on the Island of Cuba (hg. von Vera M. Kutzinski und Ottmar Ette). Summary This study is based on an editorial report, which was presented at the 2009 working conference „Alexander von Humboldt and the Hemisphere“ at Vanderbilt University (Nashville, TN). It demonstrates the textual genesis of Humboldt’s writings on Cuba through examples, which were obtained from a detailed text comparison of the three existing „original“ versions of Humboldt’s Essai politique sur l’île de Cuba. The collation was part of a larger strategy to regain philological ground for the „Humboldt in English“ (HiE) project. Since 2007 and funded with grants from the National Endowment for the Humanities, the Alexander von Humboldt-Foundation, and the Gerda Henkel Foundation, the US-German research team behind HiE has been working on new and unabridged translations and critical editions of three of Humboldt’s most significant texts from his American oeuvre.[1] The following observations will outline the most important results of this collation effort as a complementary contribution to the recent release of the HiE project’s first volume, The Political Essay on the Island of Cuba (Chicago University Press 2011), edited by Vera M. Kutzinski and Ottmar Ette. Resumen El presente artículo se basa en un estudio, que fue presentado en 2009 en la conferencia „Alexander von Humboldt and the Hemisphere“ en la Vanderbilt University (Nashville, TN). El estudio ejemplifica la génesis textual del Essai politique sur l’île de Cuba a base de una colación de las tres fuentes „originales“ del mismo texto. El estudio forma parte del proyecto editorial „Humboldt in English“ (HiE), en el cual un equipo de investigadores estadounidenses-alemanes se han propuesto publicar nuevas ediciones críticas con traducciones nuevas de tres obras claves de la obra americana de Humboldt desde 2007 (véase las informaciones en el pié de nota). La colación crea la base textual para el primer volumen de HiE, The Political Essay on the Island of Cuba (eds. Vera M. Kutzinski y Ottmar Ette), publicado en 2011.